3D meso/macroporous Ni3S2@Ni composite electrode for high-performance supercapacitor. (10th June 2018) - Chen, Shuguang; Li, Yuhan; Wu, Baoxin; Wu, Zixu; Li, Fujin; Wu, Jianghong; Liu, Peng; Li, Haibin
Abstract: Ni3 S2 @Ni composite electrode for supercapacitor is synthesized via a one-step solvothermal treatment of Ni foam at 120 °C, exhibiting a 3D meso/macroporous network structure. The structure contains Ni3 S2 nanosheets with 15–20 nm in thickness and meso/macropores with an average pore size of 24.69 nm, and its formation is regulated through the slow release of S 2− ions and the solid/liquid interfacial reactions in absolute ethanol. At a current density of 17.15 A g −1, the composite electrode demonstrates a high specific capacitance of 945.71 F g −1, and at various current densities below 17.15 A g −1, it retains capacitance retention ratios above 100% after 2000 charge/discharge cycles. A two-step oxidation and three-step reverse reduction process occurs during the reversible Faradaic reaction of Ni3 S2 in KOH aqueous solution, which is due to the valence transitions of Ni 0 in Ni3 S2 between Ni 0 and Ni 3+ . The homogeneous cracking in Ni3 S2 layer is a critical factor for achieving its long-term cycling stability, however, the cycling results in its amorphization. An asymmetric supercapacitor is assembled using Ni3 S2 @Ni composite electrode as the positive electrode and Ni foam as the negative electrode, which delivers an energy density of 55.79 Wh kg −1 at the power density of 938.98 W kg −1 . Graphical abstract: Highlights: Achieving slow release of S 2− ions in absolute ethanol during the growth of Ni3 S2 . Proposing a mechanism of solid/liquid interfacial reaction for 3D porous structure. Revealing the valence transitions between Ni 0 and Ni 3+ during the Faradaic reaction. Disclosing the importance of cracking in Ni3 S2 for its long-term cycling stability.